Some New Contributions in Nonlinear Dynamics and Applications in Engineering and Sciences - Balthazar, José Manoel [UNESP]; Gonçalves, Paulo Batista; Tusset, Angelo Marcelo; Litak, Grzegorz; Simonovic, Julijana (Springer Nature, 2025)
The book entitled Nonlinear Dynamics, Chaos, Control, Energy Transfer and their Applications in Engineering Sciences. DYCAELS 2023 comprehends a collection of 30 research papers concerning to dynamics of shells, bifurcation analysis, aerospace applications, machine systems, underwater vehicles, space robots and vehicles, nonlinear dynamics, chaos and complex systems, control and energy transfer as well as novel mathematical modeling and computational methods.